Cocopeat Marketing Strategy Through The Business Model Canvas Approach And Swot Analysis To Enhance The Competitiveness Of Environmentally Friendly Products - Solahudin, Didin; Friyatna, Galih; Zahara, Dean; Rismanto, M. Imam; Setyaningrum, Retno Purwani (SOUTHEAST ASIA JOURNAL oF GRADUATE OF ISLAMIC BUSINESS AND ECONOMICS, 2025)
Cocopeat, a processed coconut fiber product, holds significant potential as an environmentally friendly growing medium, particularly for hydroponic and horticultural agriculture. Increasing awareness of sustainable agriculture and the need for efficient alternative growing media underscore the urgency of this research, given the limited comprehensive studies on Cocopeat business development strategies at the local level. This study aims to analyze local resource-based Cocopeat business development strategies through the Business Model Canvas (BMC) approach and SWOT analysis. The method used is a descriptive qualitative approach. Data collection was carried out through literature studies and distributing questionnaires to 62 respondents from the segment of housewives and employees aged 25-40 years. Qualitative data from questionnaires and literature studies were then analyzed using content analysis and thematic analysis techniques to identify key patterns and insights. The research results indicate that the majority of respondents have a good understanding of the functions and benefits of Cocopeat and show high purchasing interest. The recommended business strategy focuses on optimizing distribution through digital channels and forming strategic local partnerships, with a strong emphasis on sustainability values and product quality assurance. These findings contribute to the development of sustainable agriculture-based entrepreneurship relevant to urban farming trends. Practically, this research can serve as a guide for Micro, Small, and Medium Enterprises (MSMEs) and startups in designing effective Cocopeat business models, and can provide input for local governments in formulating policies that support innovative and environmentally friendly local agricultural industries.